Learning and Teaching Community-Based Research : Linking Pedagogy to Practice - Etmanski, Catherine; Hall, Budd L.; Dawson, Teresa (University of Toronto Press, 2014)
« Community-Based Research, or CBR, is a mix of innovative, participatory approaches that put the community at the heart of the research process. Learning and Teaching Community-Based Research shows that CBR can also operate as an innovative pedagogical practice, engaging community members, research experts, and students. This collection is an unmatched source of information on the theory and practice of using CBR in a variety of university- and community-based educational settings. Developed at and around the University of Victoria, and with numerous examples of Indigenous-led and Indigenous-focused approaches to CBR, Learning and Teaching Community Based-Research will be of interest to those involved in community outreach, experiential learning, and research in non-university settings, as well as all those interested in the study of teaching and learning » (4e de couverture)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; autochtones; canada; orpcc; outils; pour des recherches en milieux de pratiques; pédagogie; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques; thématiques